PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAI PADA KANTOR DINAS PEMUDA, DAN OLAH RAGA KOTA MAKASSAR - Ridwan Ridwan (AkMen JURNAL ILMIAH, 2012)
One of the criteria for assessing the effectiveness of leadership is the ability to make decisions. However, criteria alone are not enough, there's another important criterion to be considered in assessing a person's leadership effectiveness. The criteria in question is a person's ability in carrying out the functions of leadership. While motivation is defined as a tendency to move, starting from a boost in self (drive) and ends with adjustment